To put it into slope intercept form, let's start by writing the equation format. It will be y=mx+b where m is the slope and b is the y intercept. Let's find the y intercept first. On the graph the line crosses the y axis at -9. Now we have one part of the equation: y=mx+(-9) aka y=mx-9. The line seems to go up one and over one from the point (0,-9). That means that the slope is then 1 since it rises 1 and runs 1. Now we have an equation of y=1x-9. But x doesn't need to have the coefficient of 1 since that is the default therefore the finished equation is y=x-9.